2004
DOI: 10.1111/j.1365-2338.2004.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the resistance inducer prohexadione‐Ca against fireblight in shoots of apple trees inoculated with Erwinia amylovora1

Abstract: Due to the lack of effective, non‐phytotoxic and publicly acceptable materials for controlling fireblight in pome fruit trees, novel strategies against Erwinia amylovora are being sought. Resistance‐inducing compounds, such as prohexadione‐Ca, represent promising alternatives. Prohexadione‐Ca is the active substance of the bioregulator Regalis, currently being introduced in several European countries and overseas. Prohexadione‐Ca reduces shoot elongation due to inhibition of gibberellin biosynthesis. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It is noteworthy that the most efficient products (C, G, and H) displaying protective effects together with defense elicitation are synthetic inputs dealing with phytohormone signaling pathway. Although the effects of product C (acibenzolar-S-methyl) and G (prohexadione-Ca) were expected, 13,36 the activity of product H gave interesting prospects. This preparation is an auxin analogue (naphthaleneacetic acid) used as a thinning agent in apple orchards.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is noteworthy that the most efficient products (C, G, and H) displaying protective effects together with defense elicitation are synthetic inputs dealing with phytohormone signaling pathway. Although the effects of product C (acibenzolar-S-methyl) and G (prohexadione-Ca) were expected, 13,36 the activity of product H gave interesting prospects. This preparation is an auxin analogue (naphthaleneacetic acid) used as a thinning agent in apple orchards.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Prohexadione-calcium (ProCa) has emerged as the primary plant growth regulator used to control vegetative growth on apples (Basak, 2004;Byers et al, 2004;Greene, 1999;Medjdoub et al, 2005;Miller, 2002;Rademacher and Kober, 2003;Unrath, 1999). It is also very effective in the control of fire blight in the shoot phase of this disease (Buban et al, 2004;Norelli and Miller, 2004;Rademacher, 2004;Rademacher and Kober, 2003;Yoder et al, 1999). The timings for the first application of ProCa to retard vegetative growth and to control fire blight are the same.…”
mentioning
confidence: 99%
“…It was also found that trees treated with prohexadione‐Ca were less infested with insect pests, such as aphids (Krawczyk & Greene, 2002), Empoasca fabae (Leahy et al. , 2002) and Cacopsylla pyri (Bubán et al. , 2004; D. Bylemans, Gorsem (BE), P. François, BASF (FR), pers.…”
Section: Reduced Disease Incidencementioning
confidence: 99%
“…Additional trials revealed that similar effects could also be induced in other, but not all, host-pathogen-combinations (Bazzi et al , 2003a,b; Table 1). It was also found that trees treated with prohexadione-Ca were less infested with insect pests, such as aphids (Krawczyk & Greene, 2002), Empoasca fabae (Leahy et al , 2002) and Cacopsylla pyri (Bubán et al , 2004; Bylemans, Gorsem (BE), P. François, BASF (FR), pers. comm.…”
Section: Reduced Disease Incidencementioning
confidence: 99%